2017
DOI: 10.1093/jjco/hyw192
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of human papillomavirus (HPV) vaccination in Asian populations from six countries: a meta-analysis

Abstract: Cervical cancer is a serious public-health problem in Asian countries. Since human papillomavirus (HPV) infection is the main risk factor for cervical cancer, HPV vaccination is considered a promising strategy to prevent cervical cancer. However, comprehensive immunogenicity and safety information for Asian populations is lacking. We searched four electronic databases including PubMed, EMBASE, Cochrane Library, and clinicaltrials.gov. We reviewed selected manuscripts and extracted the pooled relative risk (RR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 56 publications
(94 reference statements)
3
14
0
1
Order By: Relevance
“…Real-world experience in the 10 years following introduction of qHPV and bivalent HPV vaccines has demonstrated that vaccination prevents HPV infections and HPV-related disease and supports the favorable safety profile of HPV vaccines [ 9 , 33 , 34 ]. A recent meta-analysis found that HPV vaccines were highly immunogenic and well tolerated in Asian populations, consistent with international HPV vaccination studies [ 35 ].…”
Section: Discussionsupporting
confidence: 67%
“…Real-world experience in the 10 years following introduction of qHPV and bivalent HPV vaccines has demonstrated that vaccination prevents HPV infections and HPV-related disease and supports the favorable safety profile of HPV vaccines [ 9 , 33 , 34 ]. A recent meta-analysis found that HPV vaccines were highly immunogenic and well tolerated in Asian populations, consistent with international HPV vaccination studies [ 35 ].…”
Section: Discussionsupporting
confidence: 67%
“…Despite of that, differences in bivalent and quadrivalent vaccine immunogenicity among adolescent women from geographically different regions, including Finland and India, were not reported by previous clinical trials. 9,[13][14][15][16] Secondly, given that the endpoint titers for many of bivalent/Finnish recipients were not accessed, as they reached values >180,000, the reported higher HPV16/18 antibody levels induced in the bivalent/Finnish recipients are under-estimations of the true difference in antibody response. Nevertheless, our conservative estimations oversee the need to investigate the cross-neutralizing properties of the two vaccines in further details.…”
Section: Neutralizing Antibody Levels and Seroprevalencementioning
confidence: 99%
“…Lyophilized HPV pseudovirions have been delivered to murine models using microneedles ( 27 ). Studies exploring PubMed, EMBASE, Cochrane Library, and clinicaltrials.gov databases for published reports on immunogenicity and safety of bivalent and quadrivalent vaccines, specifically in Asian populations, have suggested strategies for developing vaccines that elicit enhanced HPV-16- and HPV-18- specific antibody levels ( 28 ). In light of the serious consequences of HPV-associated cancers and warts, HPV vaccination should be included in the standard childhood vaccination regimen ( 29 ).…”
Section: Introductionmentioning
confidence: 99%